Organizational Strategies for Providing Foreign Language Education Services to Adults Over 45: International Practices and Approaches - Iryna Rudnyeva (Educational Challenges)
Organizing educational services for people over the age of 45 is essential for their personal development, economic participation, social inclusion, and mental well-being. International and local legislation supports these initiatives, aiming to provide equitable and inclusive educational opportunities for all ages and to use the benefits of these people being fruitfully involved in the economic and social life of a country.